(untitled) (Research, Society and Development, 2022)
Data composing the Universal Soil Loss Equation (USLE) and the Land Surface Temperature (LST) are fundamental qualitative and quantitative factors in the use and soil conservation and are analyzed individually. This work aims to identify priority areas for recovery in the Curupaí/ MS-Brazil stream watershed. First, specific maps were prepared to this end to refer to each component factor of the USLE and Land Surface Temperature (LST) in a GIS environment. Subsequently, the annual soil loss estimation (Factor A) and surface temperature maps were reclassified to obtain the map of priority areas for recovery. As a result, the Priority Areas for Recovery Index (IAP) map identified medium and high priority areas, which the USLE and LST components alone indicated low priority. Furthermore, integrating the mentioned factors showed potential for identifying environmentally sensitive areas by analyzing multiple simultaneous parameters.